2021
DOI: 10.3390/ijerph18116012
|View full text |Cite
|
Sign up to set email alerts
|

Favorable Lip and Oral Cancer Mortality-to-Incidence Ratios in Countries with High Human Development Index and Expenditures on Health

Abstract: Background: The incidence rates of lip and oral cancer have continued to increase, and prognosis is associated with a country’s socioeconomic status. The mortality-to-incidence ratio (MIR) is a reasonable indicator of disparities in cancer screening and treatment. In this study, we aimed to understand the association between economic status and cancer prognosis. Methods: Data were obtained from the Global Cancer Observatory (GLOBOCAN) and the World Health Organization (WHO). The MIRs were compared to evaluate … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 32 publications
1
8
1
Order By: Relevance
“…This case fatality rate is higher than that reported from Uruguay [31]. Our results also revealed that the mortality rate of OC is lower than the mortality in the African countries (such as Uganda, South Africa, Egypt, Nigeria, Kenya, Tanzania) and Asian countries [24,[32][33][34]. Among these patients, the compromised patients with fourstage OC, the study deducted that factors, such as education, poor oral hygiene, and religion, were significant predictors of the OC adverse outcome and death.…”
Section: Discussioncontrasting
confidence: 40%
“…This case fatality rate is higher than that reported from Uruguay [31]. Our results also revealed that the mortality rate of OC is lower than the mortality in the African countries (such as Uganda, South Africa, Egypt, Nigeria, Kenya, Tanzania) and Asian countries [24,[32][33][34]. Among these patients, the compromised patients with fourstage OC, the study deducted that factors, such as education, poor oral hygiene, and religion, were significant predictors of the OC adverse outcome and death.…”
Section: Discussioncontrasting
confidence: 40%
“…This finding is consistent with that of a study on BC epidemiology using MIR proxy from the Global Burden of Disease study data, which found that an inverse correlation was observed between the BC MIR and HDI values, with less developed countries having BC survival statistics ( 17 ). The concept of lower cancer MIR in more developed countries and regions has been examined for several malignancies like colorectal, gastric, prostate, oral cavity, kidney, and liver cancers, all of which indicated the impact of socioeconomic development on improving cancer outcomes from an epidemiological aspect ( 12 , 13 , 16 , 19 , 21 , 24 , 51 ). The findings of this study confirmed most of the studies that used MIR to study cancer care and evaluate healthcare disparities.…”
Section: Discussionmentioning
confidence: 99%
“…The human development index (HDI) is one of the most successful measures of socioeconomic development deployed to compare health disparities in recent years ( 22 , 23 ). In addition, countries with high healthcare expenditure and government investments in healthcare have shown favorable cancer outcomes for various malignancies ( 12 , 16 , 20 , 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…From the perspective of sex differences, the disease burden in men was found to be significantly higher than that in women, consistent with the existing research results [ 60 , 61 , 62 , 63 ]. Drinking and smoking are two key risk factors that cannot be ignored [ 64 , 65 , 66 , 67 ]. The contribution of smoking and alcohol use to this cancer in men is much greater.…”
Section: Discussionmentioning
confidence: 99%